1997
DOI: 10.1097/00000478-199702000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoblastic Lymphoma Expressing Natural Killer Cell Phenotype with Involvement of the Mediastinum and Nasal Cavity

Abstract: Most CD56+ lymphomas display polymorphic and angiocentric/angiodestructive histologic features and are closely related to Epstein-Barr virus (EBV) infection. We report a 47-year-old Japanese man with CD56+ lymphoma that showed histologic features of lymphoblastic lymphoma with mediastinal and nasal involvement and an aggressive course. A sample specimen showed the histology of lymphoblastic lymphoma with a positive reaction for terminal deoxynucleotidyl transferase (TdT) but no angiocentric/angiodestructive fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 37 publications
1
33
0
Order By: Relevance
“…Furthermore, one of these seven was suffering from pulmonary aspergillosis [17], while another patient's follow-up was limited to 5 months [15]. Twenty-three of the 47 patients who succumbed to their disease failed to attain CR (and hence never experienced disease-free survival) [9,10,[13][14][15]17,[25][26][27][28][29]. Twenty-three others experienced an average disease-free survival of 8.3 months before succumbing to their disease [6,9,14,15,21,30].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, one of these seven was suffering from pulmonary aspergillosis [17], while another patient's follow-up was limited to 5 months [15]. Twenty-three of the 47 patients who succumbed to their disease failed to attain CR (and hence never experienced disease-free survival) [9,10,[13][14][15]17,[25][26][27][28][29]. Twenty-three others experienced an average disease-free survival of 8.3 months before succumbing to their disease [6,9,14,15,21,30].…”
Section: Discussionmentioning
confidence: 99%
“…34 Of note, those NK precursor tumors with or without myeloid marker express TdT detected by immunohistochemical method. [11][12][13] Because there has been no information on the TdT expression in the normal immature NK precursor, TdT expression in blastoid NK-cell lymphoma raised a debate on their cellular nature and diagnostic terminology, either lymphoblastic NK-cell lymphoma or blastoid NK-cell lymphoma. Although TdT initially was considered as a marker of immature lymphoid cells, many studies showed TdT expression in overall 18% of acute myeloblastic leukemia, and TdT positivity is more common in the immature cell types (M0, M1).…”
Section: Discussionmentioning
confidence: 99%
“…Case 2 presented with swelling of the lymph nodes of the neck. Case 1 has been previously reported [16] and also presented as a mediastinal tumor. Tumor cells were found in bone marrow in three cases (cases 1, 3, and 9).…”
Section: Resultsmentioning
confidence: 96%
“…Recently, NK phenotype of lymphoblastic lymphoma or blastic NK-cell lymphoma has been described [6,10,12,13,15,16,22,28]. Patients are predominantly middle-aged to elderly.…”
Section: Discussionmentioning
confidence: 99%